Nancy Procter-Gregg papers - Procter-Gregg, Nancy
ALsS to Procter-Gregg from Max Freyhan (1956 June) and Ernst Kris (1956 October 2) concerning a paper written by her on Sigmund Freud and Arthur Schopenhauer. Includes typewritten transcript of letter from Kris.
Typewritten transcript, in part.
Forms part of: Sigmund Freud collection.
Keywords: Freud, Sigmund, -- 1856-1939.; Freyhan, Max -- Correspondence; Kris, Ernst, -- 1900-1957 -- Correspondence; Schopenhauer, Arthur, -- 1788-1860.